Carotid Consensus Panel duplex criteria can replace modified University of Washington criteria without affecting accuracy. (April 2018) - Kim, Ann H; Augustin, Gener; Shevitz, Andrew; Kim, Hannah; Trivonovich, Michael R; Powell, Alexis R; Kumins, Norman; Tarr, Robert; Kashyap, Vikram S
The decision to intervene for internal carotid stenosis often depends on the degree of stenosis seen on duplex ultrasound (US). The aim of this study is to compare the diagnostic accuracy of two criteria: modified University of Washington (UW) and 2003 Carotid Consensus Panel (CCP). All patients undergoing US in an accredited (IAC) vascular laboratory from January 2010 to June 2015 were reviewed ( n =18, 772 US exams). Patients receiving a neck computed tomography angiography (CTA) within 6 months of the US were included in the study ( n =254). The degree of stenosis was determined by UW/CCP criteria and confirmed on CTA images using North American Symptomatic Carotid Endarterectomy Trial (NASCET)/European Carotid Surgery Trial (ECST) schema. Kappa analysis with 95% confidence intervals (CIs) were utilized to determine duplex–CTA agreement. A total of 417 carotid arteries from 221 patients were assessed in this study. The modified UW criteria accurately classified 266 (63.9%, kappa = 0.321, 95% CI 0.255 to 0.386) cases according to NASCET-derived measurements. The sensitivity, specificity, and accuracy at ≥ 60% stenosis were 65.7%, 81.3%, and 81.9%. The CCP criteria resulted in 296 (70.9%) accurate diagnoses (kappa = 0.359, 95% CI 0.280 to 0.437). At ≥ 70% stenosis, the sensitivity, specificity and accuracy were 38.8%, 91.6%, and 87.1% for NASCET. Comparison of the duplex results to ECST-derived CTA measurements revealed a similar trend (UW 53.1%, κ = 0.301 vs CCP 62.1%, κ = 0.315). The CCP criteria demonstrate a higher concordance rate with measurements taken from CTAs. The CCP criteria may be more sensitive in classifying clinically significant degrees of stenosis without a loss in diagnostic accuracy.